Use of Digital Transaction Services During the Pandemic Based on Perceptions of Community in Manado, Indonesia - Fitria Ayu Lestari Niu (UIN Sunan Gunung Djati, 2022)
This study aims to describe the perception of community in Manado City by using qualitative research methods and a phenomenological approach using OVO as digital transaction services. Data were collected through interview techniques with informants and direct observation, and data were analyzed through data reduction, data display, and conclusion. The results showed that the perception that was studied according to internal factors was through attitudes, motivations, interests, experiences, and expectations. The attitude expressed by the community of Manado City as users is that they feel happier, satisfied, easy, sophisticated, practical, and flexible. The motivation came from an offer of cashback when shopping, the prices given by tenants who work with OVO are cheaper and help the community to reduce direct interaction with people in transactions during the pandemic. The people’s interest came from their desires, the needs of the digital era like today, and encouragement from their family and co-workers. The experience so far is still very good, judging from the attitude of the informants, who are happy, and satisfied with the existence of this OVO digital transaction service. The people expect that OVO can collaborate more with tenants at malls, SMEs, and shopping places that do not yet provide digital transactions, as well as provide an official office in Manado, increase promos, and provide more payment features according to user needs, and educate the people of Manado City to switch to digital transactions.